Manajemen Pengembangan Profesionalisme Guru Agama Hindu Di Gugus Inti Sekolah Dasar Negeri Se-Kecamatan Kuta Utara Kabupaten Badung - Sukirno Hadi Raharjo; I Wayan Arisusila (Pramana: Jurnal Hasil Penelitian, 2021)
The task of the teacher is not only teaching but starting from the planning process to the assessment, as stated in the Law of the Republic of Indonesia No. 14 of 2005 concerning Teachers and Lecturers in CHAPTER I Article 1 Teachers are professional educators with the main task of educating, teaching, guiding, directing, training, assessing, and evaluating students in early childhood education through formal education, basic education, and secondary education. The theory used as the basis or basis in this research is 1) Motivation Theory, 2) Human Resource Management Theory. Data collection techniques used in this study include: observation techniques, interview techniques and document studies. The results of this study are: The Importance of Professional Development of Hindu Religion Teachers in the Core Clusters of Public Elementary Schools in North Kuta District due to the demands of Law No. 14 of 2005, Improving teacher performance, improving the quality of learning, as well as a professional teacher with the main task of educating, teaching guide and evaluate students. In the learning process the teacher before teaching prays, prepares lesson plans and uses media or teaching aids as transformation material.